Coordinate Authority Model dalam Penetapan Status Darurat Bencana Nasional di Kota Palu - Syamsul Bahri; Meldi Amijaya; Irwansyah Kamindang (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study aims to examine the procedures and criteria applied in determining the level of disaster emergency status and its potential escalation to national disaster status in Indonesia. The study draws on the context of the earthquake, tsunami, and liquefaction disasters that struck Palu City seven years ago. It employs three principal models that illustrate authority relationships among national, provincial, regency, and municipal jurisdictions within the framework of intergovernmental relations in Indonesia. The study also seeks to understand the dynamics of intergovernmental relations operating at both structural and behavioral levels by adopting Deil S. Wright’s conceptualization of intergovernmental relations, with particular emphasis on an in-depth examination of the Coordinate Authority Model. The findings reveal distinct boundaries among levels of government in the procedures and criteria used to determine disaster status. Central and local governments are connected not only through formal coordination mechanisms during periods of disaster escalation but also through a profound degree of interdependence in determining emergency status. Under certain circumstances, this interdependence generates bureaucratic tensions among governmental actors and levels of authority.